Betalains from Red Pitaya Peel (Hylocereus polyrhizus): Extraction, Spectrophotometric and HPLC-DAD Identification, Bioactivity and Toxicity Screening - Faridah, Anni; Holinesti, Rahmi; Syukri, Daimon (Pakistan Journal of Nutrition, 2015)
Betalains were extracted and analyzed from Red Pitaya Peel (Hylocereus polyrhizus). For this extraction, ethanol/water solvent systems were used. The observation such as UV-vis Spectrophotometric identification, total betalain content, HPLC-DAD analysis, antioxidant capacity, antibacterial activity and acute toxicity screening test were employed for the character of the main pigments presented in the extracts. Maximum pigment concentration (73 mg/100 g of fruit) was obtained. Four main compounds of betalain were detected by HPLC-DAD analysis with betanin as the first main compound and its concentration is 3081,97 ppm. The stability of the pigment was observed at temperature of 70°C. In addition to the antioxidant and antibacterial activities which were obtained from pigment, there was no mortality or any signs of behavioral changes or toxicity observed after oral administration of extract up to the dose level of 48500 mg/kg body weight in mice. This can be a benchmark that this pigment could be developed as a source of food colorant.